Illuminating the Onco-GPCRome: Novel G protein-coupled receptor-driven oncocrine networks and targets for cancer immunotherapy - Wu, Victoria; Raimondi, Francesco; Russell, Robert B. (The journal of biological chemistry, 2019)
G protein-coupled receptors (GPCRs) are the largest gene family of cell membrane-associated molecules mediating signal transmission, and their involvement in key physiological functions is well-established. The ability of GPCRs to regulate a vast array of fundamental biological processes, such as cardiovascular functions, immune responses, hormone and enzyme release from endocrine and exocrine glands, neurotransmission, and sensory perception (e.g. vision, odor, and taste), is largely due to the diversity of these receptors and the layers of their downstream signaling circuits. Dysregulated expression and aberrant functions of GPCRs have been linked to some of the most prevalent human diseases, which renders GPCRs one of the top targets for pharmaceutical drug development. However, the study of the role of GPCRs in tumor biology has only just begun to make headway. Recent studies have shown that GPCRs can contribute to the many facets of tumorigenesis, including proliferation, survival, angiogenesis, invasion, metastasis, therapy resistance, and immune evasion. Indeed, GPCRs are widely dysregulated in cancer and yet are underexploited in oncology. We present here a comprehensive analysis of GPCR gene expression, copy number variation, and mutational signatures in 33 cancer types. We also highlight the emerging role of GPCRs as part of oncocrine networks promoting tumor growth, dissemination, and immune evasion, and we stress the potential benefits of targeting GPCRs and their signaling circuits in the new era of precision medicine and cancer immunotherapies.
Gesehen am 04.12.2019